IMPLEMENTASI ARTIFICIAL INTELEGENCE (AI) DALAM DUNIA PENDIDIKAN DI ERA SOCIETY 5.0 - Tri Kristianti (Prosiding Temu Ilmiah Nasional Guru, 2023)
Era Society 5.0 becomes the era that provides the widest opportunity to the needs ofmodern Technology-based Science (IPTEK) to support the economic, health, and educationsectors. The application of modern technology such as Artificial Intelligence (AI), Robots, andthe Internet of Things (IoT) is necessary to fulfill the needs of society in terms of comfort,flexibility, and convenience. This research aims to describe the involvement of AI applications inthe Education context based on the learners’ needs. The AI technology in this research is limitedto those which the researcher has applied. The method used in this research is descriptivequalitative by using the review literature technique through e-books, scientific journals, articles,and other relevant documents to gain the primary data. The result of this research is significantfor future research to conduct in-depth studies about AI involvement in the Education context forthe society of 5.0.